Rural Psychology 1983
DOI: 10.1007/978-1-4613-3512-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Social Psychology and Religious Fundamentalism

Abstract: Religion is obviously shaped by the social context within which it exists. Hence, one might expect some legitimacy to the concept of rural religion. Furthermore, if there is even partial truth to the claims that, relative to more cosmopolitan cultures, rural cultures are less heterogeneous, less tolerant of divergencies in belief and action, and less abstract in their conceptualizations, then these claims should hold true to the same extent for rural religion as they do for rural culture in general. In this se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 105 publications
0
35
0
Order By: Relevance
“…This tension may come from the -institutional reputation‖ that mainstream educational and scientific institutions are involved in liberalizing and secularizing society (Gross and Fosse 2012;Wuthnow 1988, 154-72). Many conservative Protestants place trust in God in opposition to confidence in science, and view scientific knowledge as a form of sinful hubris (Hood, Hill, and Williamson 2005;Noll 1994). …”
Section: Religion and Firearm Access Among Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This tension may come from the -institutional reputation‖ that mainstream educational and scientific institutions are involved in liberalizing and secularizing society (Gross and Fosse 2012;Wuthnow 1988, 154-72). Many conservative Protestants place trust in God in opposition to confidence in science, and view scientific knowledge as a form of sinful hubris (Hood, Hill, and Williamson 2005;Noll 1994). …”
Section: Religion and Firearm Access Among Adolescentsmentioning
confidence: 99%
“…Additionally, some scholars argue that the combination of conservative Protestants' theological or moral certainty and tension with mainstream society hampers open and systematic thinking about the multifaceted nature of human behavior (Hood, Hill, and Williamson 2005). For example, rather than consider structural explanations of human behavior, many conservative Protestants reduce behavior to beliefs about God's mysterious will, sinful human choices, or the decline of the nuclear family 7 (Emerson, Smith, and Sikkink 1999).…”
Section: Religion and Firearm Access Among Adolescentsmentioning
confidence: 99%
“…Scholars of religious fundamentalism count belief in scriptural inerrancy and literalism as key identifiers of fundamentalism (Almond et al, 1995;Hood et al, 2005). Survey researchers frequently use literal interpretation of the Bible as a measure of Christian fundamentalist orientation (Jelen et al, 1990), with variation in biblical literalism found within both traditionally conservative and liberal denominations (Village, 2005;Woodberry and Smith, 1998).…”
Section: Biblical Literalismmentioning
confidence: 99%
“…Pienaar et al explain that conservative and fundamentalist belief gives adolescents a stable internal structure to develop well-being, especially in times of great social change. Hood, Hill and Williamson (2005) have a similar argument. They argue that fundamentalism is a meaning system, derived from historical tradition and drawing heavily on sacred text, which allows people to persevere in a challenging environment and gives them a way and framework to make sense of themselves and their relationship with the world.…”
Section: Prediction Of Life Satisfactionmentioning
confidence: 61%